Utilisation of waste medicine wrappers as an efficient low-cost electrode material for microbial fuel cell. Issue 10 (28th April 2020) - Noori, Md. T.; Bhowmick, G. D.; Tiwari, B. R.; Das, I.; Ghangrekar, M. M.; Mukherjee, C. K.
ABSTRACT: Waste generation from healthcare facilities now has become a concerning issue as it contain plastic and metals. Medicine wrappers are one of the major portions of healthcare solid waste, which impel intensive solid waste management practice due to fewer possibilities of deriving by-products. However, it can be recycled and used as an electrode material in microbial fuel cells (MFCs). An electrode material for application in MFCs is a crucial component, which governs total fabrication cost as well as power recovery, thus a cost-effective, stable and durable electrode is essential. In this endeavour, a new metallic (aluminium) waste material, a waste medicine wrapper (WMW), was evaluated for feasibility to be used as anode/cathode in MFCs. Based on the stability test under corrosive environment (1 N KCl), the WMW electrode sustained a maximum current of 46 mA during cyclic voltammetry (CV) and noted only 14% reduction in current at an applied voltage of +0.4 V after 2500 s in chronoamperometry, indicating its good stability. Power recovery from MFC using WMW was higher than the MFC using bare carbon felt as an anode (27 vs. 21 mW/m 2 ). The entire analytical test results viz. CV, electrochemical impedance spectroscopy and power performance established WMW as an excellent anode rather than cathode material. GRAPHICAL ABSTRACT: